Dziedzictwo kulturowe a miejsce i czas - Petrykowski, Piotr (Wydawnictwo Naukowe UAM, 2013)
If the development of cultural identity is seen as one of the signifi cant features of contemporary education, the process is conditioned on the sense of being rooted in culture. This sense is crucially linked to cultural heritage. Key for these refl ections is the aspect of an identifi cation with a place as a function of time. Three fundamental issues converge here. One is the differences in the experience of time arising from age. Another considers the time necessary for being rooted and at the same time the question of experience intensity. Belonging to a place is an experience different from possessing and cherishing a sense of place. Finally, the third issue in the analysis of the place as a function of time relates to the intensity of changes and a return to, or a yearning for the past. The intensity of changes and the possibility of instantaneous movement in space, all these processes and patterns prevent the human being nowadays from taking root; his or her experience and sense of place is superfi cial. The time-consuming process of developing a sense of belonging, of being rooted, is in principle a process that leads to an emergence of a subconscious state which denotes a certain level of identifi cation with a given area. The human being nowadays has too little time for this process, though. This is also linked to the signifi cance of the transmission of cultural heritage, which is not given and is not identical to the legacy of blood.
Cultural Heritage vs. Place and Time
Keywords: cultural heritagecultural heritage; cultural heritage; time; space; place (loci); cultural identity